PENGEMBANGAN BUKU DIGITAL CREATIVE WRITING: BLENDED LEARNING BERBASIS PROYEK TERINTEGRASI KECAKAPAN 6C - Levandra Balti; Winda T Trisnwati; Tiara Monika (LPPM Universitas Muhammadiyah Muara Bungo, 2023)
This development aims to develop and evaluate digital books with a blended learning approach that is integrated with 6C skills in the English creative writing: drama and theater course. This course aims to improve students' ability to write drama and theater scripts in English while developing important skills that are relevant in a language-learning context. This research design is a research and development design that uses a 4D model. The stages of this research are the define stage, design stage, develop stage, and disseminate stage. The results of this research show that digital blended learning books with a project approach and integration of 6C skills have a positive impact on students' ability to write drama and theater scripts in English. Students also demonstrated improvements in developing 6C skills, including the ability to collaborate, communicate effectively, and think critically. This research provides recommendations for further development in the use of digital blended learning books in the English Creative Writing Drama and Theater courses, as well as increasing the integration of 6C skills in language learning contexts. The findings of this research can be an important contribution to the development of more innovative curricula and teaching methods in English education and the development of student skills.